Cloudy with a chance of meatballs [videorecording (DVD)] - Lord, Phil, 1977-; Lord, Phil, 1977-; Miller, Chris, 1975-; Miller, Chris, 1975-; Barrett, Judi (Sony Pictures Home Entertainment, 2010)
Flint Lockwood is a young inventor who dreams of creating something that will improve everyone's life. Sam Sparks is a weathergirl covering the town's weather phenomenon, but chooses to hide her intelligence behind a perky exterior. Tim Lockwood is Flint's technophobic father. Brent is the town bully who has plagued Flint since childhood. Mayor Shelbourne exploits Flint's newest invention so he can put the town, and more importantly himself, on the map. By-the-rules town cop Earl Devereaux has a rule-breaking son, Cal. In a town where food drops from the sky like rain, Flint hopes to create something that will change everyone's life. However, when the weather takes a turn for the worse, the residents of the town of Chewandswallow will find their eating habits have drastically changed.